2017
DOI: 10.1115/1.4036408
|View full text |Cite
|
Sign up to set email alerts
|

Three-Stage Feedback Controller Design With Applications to Three Time-Scale Linear Control Systems

Abstract: This paper presents a new technique for design of full-state feedback controllers for linear dynamic systems in three stages. The new technique is based on appropriate partitioning of the linear dynamic system into linear dynamic subsystems. Every controller design stage is done at the subsystem level using only information about the subsystem (reduced-order) matrices. Due to independent design in each stage, different subsystem controllers can be designed to control different subsystems. Partial subsystem lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hence, the use of singular perturbation techniques may not be feasible always. Instead, the use of similarity transformations to derive decoupled subsystems could be a more promising method (Gajic et al, 2017). Because of this, the proposed two-stage MSFC design uses similarity transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the use of singular perturbation techniques may not be feasible always. Instead, the use of similarity transformations to derive decoupled subsystems could be a more promising method (Gajic et al, 2017). Because of this, the proposed two-stage MSFC design uses similarity transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Terms 1 , 2 , 3 ,B 2 ,B 3 , α 12 ,α 13 andβ 2 are spelled out in the Appendix A.2. Comments on the required computational power needed to solve those iterative equations and achieved precision and convergence rate are provided in [39].…”
Section: Multistage Control Techniquementioning
confidence: 99%
“…Coupling analysis showed that some sort of the decoupling control strategy would optimize the system performance. The recent approach presented in [38][39][40], tackle the coupling interference between physical variables represented as states in the model, by investigating PEMFC subsystems as systems with multiple time scales. It was suggested and demonstrated in [41] that PEMFC has at least three distinct characteristic time scales, processes with response time less than 1s, approximately 100s and more than 1000s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation